Optimization and evaluation of microwave-assisted curcumin-loaded nanostructured lipid carriers: a green approach - Sunidhi Lohan; Ravinder Verma; Deepak Kaushik; Meenakshi Bhatia (SpringerOpen, 2023)
Abstract Background The goal of current research work is to develop and optimize curcumin-encapsulated nanostructured lipid carriers and to enhance therapeutic effect of curcumin after oral administration. Method Curcumin-loaded nanostructured lipid carriers were developed by a single-step one-pot microwave-assisted technique. The preparation of curcumin-loaded nanostructured lipid carriers was optimized by employing two factors and three levels central composite design (Design Expert® software) taking concentration of lipid blend and surfactant as independent variables and particle size, polydispersity index, and zeta potential as dependent variables, to investigate the effect of formulation ingredients on the physicochemical characteristics of nanostructured lipid carriers. The optimized batch was investigated by Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction, high-resolution transmission electron microscopy, in vitro drug release, stability studies, cytotoxicity, and in vivo anthelmintic studies. Results The average particle size, polydispersity index, and zeta potential of the optimized batch were found to be 144 nm, 0.301, and − 33.2 mV, respectively, with an entrapment efficiency of 92.48%. The results of high-resolution transmission electron microscopy confirmed spherical shape of particles. In vivo antiparasitic studies included determining the duration of paralysis and eventual death of earthworms in the presence of test samples. The results of in vivo studies showed good anthelmintic potential for curcumin-loaded nanostructured lipid carriers as compared to albendazole in different concentrations. Cytotoxicity studies also confirmed the formulation to be nontoxic to Vero cells. In vitro drug release study showed 90.76 ± 0.01% release of curcumin in 24 h by following the Korsmeyer-Peppas model of release kinetics. Conclusion The aforementioned results imply that microwave-developed nanostructured lipid carriers could be promising drug carriers and will aid in their fabrication for oral administration as a possible alternative for the treatment of other parasitic infections. Graphical Abstract